2019
DOI: 10.1080/02705060.2018.1542352
|View full text |Cite
|
Sign up to set email alerts
|

Faster response to water level increase facilitatesSalix cavalerieisurvival in Lake Erhai

Abstract: The roles that adventitious roots play in flooding tolerance have been well-studied in willows, while which of the maximum height of adventitious roots and the abundance of adventitious roots in willows is more important for their flooding tolerance is not well known. In this study, we analyzed the effects of adventitious roots on the flooding tolerance of Salix cavaleriei by comparing the maximum height of adventitious roots and the abundance of adventitious roots in dead and live willows along a flooding gra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…As far as plants are concerned, we believe that the uprooting or the floating mat formation of an emergent macrophyte is greatly influenced by the three factors (the plant root:shoot biomass ratio, the plant volume:mass ratio, and the angle between the plant and the horizontal plane) mentioned above, though other mechanisms may play important roles in these functions [23][24][25]. In our field survey, we found that the emergent community in Lake Erhai had changed from a Phragmites australis, Typha orientalis and Acorus calamus polydominant community to a Zizania latifolia monodominant community over the past decades during a long period of increasing water level, usually over 80 cm (and even 100 cm in some specific years) than before since 2003 by water level regulation, [20,26,27]. Furthermore, an increasing number of floating mats had formed and distributed throughout the lake's littoral zone (Figure 1).…”
Section: Introductionmentioning
confidence: 61%
See 1 more Smart Citation
“…As far as plants are concerned, we believe that the uprooting or the floating mat formation of an emergent macrophyte is greatly influenced by the three factors (the plant root:shoot biomass ratio, the plant volume:mass ratio, and the angle between the plant and the horizontal plane) mentioned above, though other mechanisms may play important roles in these functions [23][24][25]. In our field survey, we found that the emergent community in Lake Erhai had changed from a Phragmites australis, Typha orientalis and Acorus calamus polydominant community to a Zizania latifolia monodominant community over the past decades during a long period of increasing water level, usually over 80 cm (and even 100 cm in some specific years) than before since 2003 by water level regulation, [20,26,27]. Furthermore, an increasing number of floating mats had formed and distributed throughout the lake's littoral zone (Figure 1).…”
Section: Introductionmentioning
confidence: 61%
“…In general, the formation of an emergent floating mat demands two habitat requirements: shelter from wind and wave action and stability of water level fluctuations [11]. The adaptations of macrophytes to deep water include increases in plant height, branch length, shoot internodes and shoot:root biomass ratio, and reductions in belowground biomass and branch number [2,6,7,19,20]. All these adaptations can be demonstrated by the root:shoot biomass ratio of a plant to some degree.…”
Section: Introductionmentioning
confidence: 99%